Gabapentin-induced aquagenic wrinkling of the palms. - SU KÜÇÜK, ÖZLEM; Emiroglu, N; Cengiz, FP; Su, ÖZLEM SU; Onsun, N (My University, 2017)
Aquagenic keratoderma (AK) or aquagenic wrinklingis a rare palmoplantar skin disease. It is sporadic orhereditary condition. It appears in childhood or youngadulthood and it is seen as multiple asymptomaticsmall shiny papules on the peripheral margin ofpalms and/or soles after submersion in water. Thepathogenesis and etiology of ASA remains unclear.Drugs sometimes trigger AK. Herein, we present thecase of a 29-year-old man who had begun treatmentwith gabapentin three weeks before the onset of hiscutaneous symptoms.
Keywords: Aquagenic wrinkling; Gabapentin